2014
DOI: 10.1186/1750-9378-9-44
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Bcl-2 and Bcl-xL by viral proteins as a possible cause of cancer

Abstract: The Bcl proteins play a critical role in apoptosis, as mutations in family members interfere with normal programmed cell death. Such events can cause cell transformation, potentially leading to cancer. Recent discoveries indicate that some viral proteins interfere with Bcl proteins either directly or indirectly; however, these data have not been systematically described. Some viruses encode proteins that reprogramme host cellular signalling pathways controlling cell differentiation, proliferation, genomic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 143 publications
(174 reference statements)
2
17
0
Order By: Relevance
“…The protein encoded by the Bax gene, together with other antiapoptotic proteins, can be formed during the formation of Bcl-2 heterologous dimers, with the function of antagonizing the function of Bcl-2 in order to promote cell apoptosis (14). Besides, structural changes in various organelles and in the cytoplasmic membrane, particularly in the mitochondrial outer membrane, as well as changes in the interaction between the antiapoptotic Bcl-2 protein and the membrane, may cause the loss of antiapoptotic proteins responsible for apoptosis inhibition, resulting in the loss of function of these organelles and the release of several apoptosis-promoting factors, eventually leading to cell apoptosis (14). The present study demonstrated that icaritin inhibits Bcl-2 protein expression in COLO-205 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein encoded by the Bax gene, together with other antiapoptotic proteins, can be formed during the formation of Bcl-2 heterologous dimers, with the function of antagonizing the function of Bcl-2 in order to promote cell apoptosis (14). Besides, structural changes in various organelles and in the cytoplasmic membrane, particularly in the mitochondrial outer membrane, as well as changes in the interaction between the antiapoptotic Bcl-2 protein and the membrane, may cause the loss of antiapoptotic proteins responsible for apoptosis inhibition, resulting in the loss of function of these organelles and the release of several apoptosis-promoting factors, eventually leading to cell apoptosis (14). The present study demonstrated that icaritin inhibits Bcl-2 protein expression in COLO-205 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The family is divided into two categories: The first one comprises antiapoptotic proteins, mainly Bcl-2, Bcl-extra large, Bcl-W, A1/Bfl-1, myeloid cell leukemia 1 and Boo, while the second one comprises proapoptotic proteins, including Bcl-2 associated X protein (Bax), Bcl-2 homologous antagonist/killer, Bcl-2 related ovarian killer, Bcl-x, BH3 interacting-domain death agonist and Bcl-2-associated death promoter (14). The Bcl-2 protein can inhibit cell apoptosis, but is unable to promote cell proliferation, in cancer cells (13).…”
Section: Introductionmentioning
confidence: 99%
“…This NLRP1 polymorphism was previously associated to an augmented IL-1ß and IL-18 processing [Levandowski et al, 2013] and, interestingly, to breast cancer in a GWAS study [Gao et al, 2012], suggesting that the NLRP1-inflammasome activation could be beneficial to the host against cancer development. Of note, NLRP1 interacts with Bcl-2 and Bcl-X and it is involved in the apoptotic pathway [Bruey et al, 2007;Faustin et al, 2009], which is affected in transformed HPVþ keratinocytes [Alibek et al, 2014].…”
mentioning
confidence: 99%
“…Programmed cell apoptosis prevents the uncontrolled proliferation of potentially tumorigenic cell and thus serves as a natural barrier to cancer development [23,24]. The apoptotic trigger is controlled by counterbalancing of pro-apoptotic and anti-apoptotic proteins [25,26]. In this study, adenos-ine induces apoptosis of Hela and SiHa cells.…”
Section: Discussionmentioning
confidence: 80%